The Role of HR Management in Creating an Effective Work Environment at PT Sinar Maju Indonesia - Muliadi, Dedi (Journal Business Inovation, Accounting and Management, 2025)
This study aims to analyze the role of human resource management (HR) in creating an effective work environment at PT Sinar Maju Indonesia. The method used is a quantitative approach with data collection through questionnaires that are distributed to 60 employees from various divisions. The aspects examined include recruitment, training and development, reward systems, and internal communication. The results of the study show that HR management has a significant role in forming a conducive work environment. As many as 82% of respondents stated that regular training improves their competence and confidence. In addition, 75% of respondents think that a good internal communication system helps reduce conflict and improve collaboration between teams. Linear regression analysis showed that the HR management variable had a positive effect on the effectiveness of the work environment with a determination coefficient value (R²) of 0.68. These findings confirm that a structured and sustainable HR strategy is essential in creating a productive and harmonious work climate. This study recommends strengthening employee development programs and increasing communication openness between organizational levels.